2020
DOI: 10.1002/adfm.202000842
|View full text |Cite
|
Sign up to set email alerts
|

3D MXene Architectures for Efficient Energy Storage and Conversion

Abstract: 2D transition metal carbides and/or nitrides (MXenes), by virtue of high electrical conductivity, abundant surface functional groups and excellent dispersion in various solvents, are attracting increasing attention and showing competitive performance in energy storage and conversion applications. However, like other 2D materials, MXene nanosheets incline to stack together via van der Waals interactions, which lead to limited number of active sites, sluggish ionic kinetics, and finally ordinary performance of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
249
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(263 citation statements)
references
References 261 publications
(185 reference statements)
0
249
0
Order By: Relevance
“…Nevertheless, the deficiencies of easy self-aggregation, unsatisfying ions accessibility, and low theoretical capacity are generally inevitable for MXenes, because of the hydrogen bonds or van der Walls interactions between the laminated adjacent layers. Particularly, the performance is yet far to be satisfied when used as the anode of the batteries with larger alkali-metal ions [ 3 , 11 ]. It is thus requested the design of advanced heterostructures to address the above-mentioned challenges in the electrochemical energy storage applications [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the deficiencies of easy self-aggregation, unsatisfying ions accessibility, and low theoretical capacity are generally inevitable for MXenes, because of the hydrogen bonds or van der Walls interactions between the laminated adjacent layers. Particularly, the performance is yet far to be satisfied when used as the anode of the batteries with larger alkali-metal ions [ 3 , 11 ]. It is thus requested the design of advanced heterostructures to address the above-mentioned challenges in the electrochemical energy storage applications [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intercalation can also be used in the fabrication of supercapacitors, between MXenes and the intercalants. MXenes, which are generally prepared from MAX phases comprised of layered ternary carbides with the formula is M n+1 X n T z (n is an integer between 1 and 4) [133][134][135][136] where M is an early transition metal, X is carbon and/or nitrogen, and T embodies various terminations such as fluorine, hydroxyl, and/or oxygen atoms 120,121 . Shen et al 137 reported improved electrical conductivity and electrochemical performance when carbon-intercalated Ti 3 C 2 T x MXene (Ti 3 C 2 T x /C) was used as the active electrode material of supercapacitors.…”
Section: Electrochemical Capacitorsmentioning
confidence: 99%
“…The newly reported electrical conductivity of the Ti 3 C 2 T x MXene has reached as high as 15,100 S cm –1 [ 66 ], and moreover, high transparency, outstanding flexibility and adjustable WF are associated with it [ 67 69 ]. All these properties make Ti 3 C 2 T x suitable as electrodes in optoelectronic devices including solar cells.…”
Section: Applications Of Mxenes In Solar Cellsmentioning
confidence: 99%